2009
DOI: 10.1083/jcb.200812022
|View full text |Cite
|
Sign up to set email alerts
|

Dbf2–Mob1 drives relocalization of protein phosphatase Cdc14 to the cytoplasm during exit from mitosis

Abstract: Exit from mitosis is characterized by a precipitous decline in cyclin-dependent kinase (Cdk) activity, dissolution of mitotic structures, and cytokinesis. In Saccharomyces cerevisiae, mitotic exit is driven by a protein phosphatase, Cdc14, which is in part responsible for counteracting Cdk activity. Throughout interphase, Cdc14 is sequestered in the nucleolus, but successful anaphase activates the mitotic exit network (MEN), which triggers dispersal of Cdc14 throughout the cell by a mechanism that has remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
127
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(130 citation statements)
references
References 47 publications
1
127
1
1
Order By: Relevance
“…In vitro studies showed that Dbf2 is basophilic, preferring to phosphorylate serine or threonine residues that are three residues C-terminal to arginine (R-X-X-[S/T]) (Mah et al 2005). This short consensus motif, which is shared by other basophilic kinases, has been borne out for several in vivo substrates (Mohl et al 2009;Oh et al 2012).…”
Section: Menmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies showed that Dbf2 is basophilic, preferring to phosphorylate serine or threonine residues that are three residues C-terminal to arginine (R-X-X-[S/T]) (Mah et al 2005). This short consensus motif, which is shared by other basophilic kinases, has been borne out for several in vivo substrates (Mohl et al 2009;Oh et al 2012).…”
Section: Menmentioning
confidence: 99%
“…Mob1-Dbf2/Cdc14 release positive feedback loop: In vitro and in vivo studies indicate that Mob1-Dbf2 directly drives cytoplasmic accumulation of Cdc14 by phosphorylating it at sites near its C-terminal nuclear localization sequence (NLS) (Mohl et al 2009). This inhibits the NLS's function, shifting Cdc14's distribution from the nucleus to the cytoplasm and thus allowing it to remove CDK phosphorylations on cytoplasmic proteins.…”
Section: Menmentioning
confidence: 99%
“…Initially, it was unclear how the Mob1p/Dbf2p complex transmitted the signal to Cdc14p. However, Mohl et al (2009) recently showed that the Mob1p/Dbf2p complex can directly phosphorylate Cdc14p, an event that is sufficient to trigger the relocalisation of Cdc14p at the end of mitosis [34]. To sum up, activation of the Tem1p/Cdc15/Mob1p/Dbf2p/Cdc14p cascade results in CDK1 inactivation, which enables mitotic exit.…”
Section: Mitotic Exit Network (Men) In S Cerevisiaementioning
confidence: 99%
“…We previously demonstrated that Cbk1 is a hyperphosphorylated protein, and we proposed a model in which this phosphorylation inhibits Cbk1's function in vivo (29). One important function of the MEN is to reverse the phosphorylations performed by the mitotic cyclin-dependent kinase Cdc28/Cdk1 (39,46,67). Thus, at the cdc15-2 arrest, mitotic CDK phosphorylations may persist and might contribute to the inhibition of Cbk1.…”
Section: Vol 31 2011 Mitotic Control Of the Yeast Ram Network 727mentioning
confidence: 99%
“…The MEN, initiated by activation of the GTPase Tem1, activates a signaling cascade of kinases, including Cdc15 and Dbf2/Mob1 (3,6,25,39,53,66). Dbf2/Mob1 phosphorylates Cdc14 to inactivate its nuclear localization signal (NLS), promoting release of Cdc14 into the cytoplasm (46). Cytoplasmic Cdc14 dephosphorylates CDK targets to promote mitotic exit and the final events of cell division (7,61,67).…”
mentioning
confidence: 99%